If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.04(y-2)+0.12y=0.20y-0.4
We move all terms to the left:
0.04(y-2)+0.12y-(0.20y-0.4)=0
We add all the numbers together, and all the variables
0.12y+0.04(y-2)-(0.20y-0.4)=0
We multiply parentheses
0.12y+0.04y-(0.20y-0.4)-0.08=0
We get rid of parentheses
0.12y+0.04y-0.20y+0.4-0.08=0
We add all the numbers together, and all the variables
-0.04y+0.32=0
We move all terms containing y to the left, all other terms to the right
-0.04y=-0.32
y=-0.32/-0.04
y=+8
| 75x=6.25=90x=4.75 | | z+23=6 | | w=A5 | | 5x-7x-15=-2x+2-15 | | 84=-2(-6x-6) | | 3(x–1)=3x–1 | | 15x/8+3/4=2x | | 3^2x-10(3^x+1)+81=0 | | y-3.2=8.83 | | 2x-(5-x)=13+2 | | x+7–4x=19–2x | | 3y+y=29.5 | | -4+23+x+21=2 | | 7x+10-4x+5=4x+1-2x | | 5n-14=9n+18 | | -2x=114 | | 10=2(12+x/5) | | X-2=6x-2/4 | | 20/x=5/x | | 3=c5+2 | | 7(14–x)=3x+18 | | (7x-4)–(5x+2)=(10x+6)–(7x-4) | | x+2x+4=86 | | -2(t+3)=24-5t | | 3g+5=20 | | 4(6j-15)=6(28-2j) | | 3(c-1)+2(3c+1)=-3c+1) | | 4a+3=4a | | 3n+6=n+8+2n–2 | | y=-(0)^2+25 | | 88=9x+43 | | x+23=×+54 |